2018
DOI: 10.1158/1541-7786.mcr-17-0270
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Gain of 16p13.3 in Prostate Cancer Predicts Poor Clinical Outcome after Surgical Intervention

Abstract: Identifying tumors with high metastatic potential is key to improving the clinical management of prostate cancer. Recently, we characterized a chromosome 16p13.3 gain frequently observed in prostate cancer metastases and now demonstrate the prognostic value of this genomic alteration in surgically treated prostate cancer. Dual-color FISH was used to detect 16p13.3 gain on a human tissue microarray representing 304 primary radical prostatectomy (RP) cases with clinical followup data. The results were validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…The advantage of this combinatorial approach was further evidenced by an increase of the C-index, which reached its maximum when coupled with the CAPRA-S score risk groups. Interestingly, the PTEN deletion status identified patients of CAPRA-S low-risk group who have an increased risk of biochemical recurrence, while the 16p13.3 gain status alone did not further stratify the low-risk group as we reported [18]. These results are in agreement with previous studies showing that combinations of genomic features such as gene expression changes and copy number alterations, including PTEN deletion status, can add prognostic information to the CAPRA-S score [30,31].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The advantage of this combinatorial approach was further evidenced by an increase of the C-index, which reached its maximum when coupled with the CAPRA-S score risk groups. Interestingly, the PTEN deletion status identified patients of CAPRA-S low-risk group who have an increased risk of biochemical recurrence, while the 16p13.3 gain status alone did not further stratify the low-risk group as we reported [18]. These results are in agreement with previous studies showing that combinations of genomic features such as gene expression changes and copy number alterations, including PTEN deletion status, can add prognostic information to the CAPRA-S score [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…We recently reported that the 16p13.3 gain was associated with aggressive clinicopathologic features of prostate cancer as well as an increased risk of biochemical recurrence and distant metastases in the same radical prostatectomy specimens surveyed here for PTEN deletion [18]. Moreover, the 16p13.3 gain status improved the stratification of patients with intermediate and high risk of disease progression based on their CAPRA-S score.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations